Analysis of Student Reading Interest in the Implementation of Literacy Culture at SD Negeri 1 Gondanglor - Desta Nur Rahmawati; Erna Eka Widiyawati; Zuhrotun Nisak; Syamsul Syamsul (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Students interest in reading is currently declining and many are caused by several factors. The problem of education in Indonesia is still focused on the low level of student literacy. This is caused by a lack of interest in reading in students, which is largely influenced by technological advances and the lack of the role of parents and teachers in providing motivation. In fact, by doing reading activities, a person can get a lot of new things, can provide encouragement in finding new information and can broaden his knowledge. The aims of this study were: (1) to find out students' reading interest in SD Negeri 1 Gondanglor (2) to find out the application of literacy culture in SD Negeri 1 Gondanglor (3) to find out students' reading interest with the application of literacy culture in SD Negeri 1 Gondanglor. In research using qualitative research. From the results of research at SD Negeri 1 Gondanglor it can be seen that students' interest in reading at SD Negeri 1 Gondanglor falls into the